Neighbourhood approximation forests. - Konukoglu, Ender; Glocker, Ben; Zikic, D.; Criminisi, Antonio (2012 Medical Image Computing and Computer-Assisted Intervention, 2012)
Methods that leverage neighbourhood structures in high-dimensional image spaces have recently attracted attention. These approaches extract information from a new image using its “neighbours” in the image space equipped with an application-specific distance. Finding the neighbourhood of a given image is challenging due to large dataset sizes and costly distance evaluations. Furthermore, automatic neighbourhood search for a new image is currently not possible when the distance is based on ground truth annotations. In this article we present a general and efficient solution to these problems. “Neighbourhood Approximation Forests” (NAF) is a supervised learning algorithm that approximates the neighbourhood structure resulting from an arbitrary distance. As NAF uses only image intensities to infer neighbours it can also be applied to distances based on ground truth annotations. We demonstrate NAF in two scenarios: i) choosing neighbours with respect to a deformation-based distance, and ii) age prediction from brain MRI. The experiments show NAF’s approximation quality, computational advantages and use in different contexts.